Quantification of a bacterial secondary metabolite by SERS combined with SLM extraction for bioprocess monitoring. Issue 23 (8th November 2017) - Morelli, Lidia; Andreasen, Sune Zoëga; Jendresen, Christian Bille; Nielsen, Alex Toftgaard; Emnéus, Jenny; Zór, Kinga; Boisen, Anja
Abstract : The yield of a bacterial secondary metabolite was quantified using SERS-based sensing combined with a SLM μfluidic device enabling sample extraction and enrichment. Abstract : During the last few decades, great advances have been reached in high-throughput design and building of genetically engineered microbial strains, leading to a need for fast and reliable screening methods. We developed and optimized a microfluidic supported liquid membrane (SLM) extraction device and combined it with surface enhanced Raman scattering (SERS) sensing for the screening of a biological process, namely for the quantification of a bacterial secondary metabolite, p -coumaric acid (pHCA), produced by Escherichia coli . The microfluidic device proved to be robust and reusable, enabling efficient removal of interfering compounds from the real samples, reaching more than 13-fold up-concentration of the donor at 10 μL min −1 flow rate. With this method, we quantified pHCA directly from the bacterial supernatant, distinguishing between various culture conditions based on the pHCA production yield. The obtained data showed good correlation with HPLC analysis.